Gamification in training and development processes: perception on effectiveness and results (REGE Revista de Gestão, 2021)
Purpose – Gamification is the use of game elements in different contexts. It is also a tool with potentialapplication in several areas, including training and development. From this reference, this study has a mainobjective to identify a perception of efficiency and the measurable results in the process of gamification intraining and development actions.Design/methodology/approach – The quantitative stage of the research sought to investigate theperception of efficiency of professionals who have already undergone gamified training, collected through anonline form with responses on a Likert scale and treated with the Minitab Statistical Software. The qualitativestage, on the other hand, identifies the perception of results through classification with professionals whodevelop gamified training, with the results found in the content analysis techniques.Findings – The compiled results confirmed the presence of engagement and its influence on motivation as oneof the advantage points for the application of gamification. It was also possible to find in these results therelevance of design care for the game/training interaction to work effectively.Originality/value – Among the trends of greatest incidence found in the research, are the possibility ofassociating gamification with virtual reality and augmented reality, as well as with simulators to enhance theexperience lived by the player during training